Beyond the Death of God Religion in 21st Century International Politics - RAUDINO, Simone; Sohn, Patricia (University of Michigan Press, 2022)
This volume offers a nuanced picture with specific instances of religion and politics in Muslim, Jewish, Christian, Buddhist, and Hindu contexts, broadly presenting the phenomenon of religion and politics via country and thematic case studies. Qualitative, quantitative, material, philosophical, and theological analyses draw upon social theory to show how (and why) religion matters deeply in each time and place. The authors and contributors demonstrate that religion is a significant force that drives societies and polities around the world, and that a radical change in the Western understanding of value-driven global politics is needed. Beyond the Death of God offers new, local voices to Western audiences-through essays that suggest the need for an appreciation of Divinity as a quintessence holding a significant place in the hearts, minds, social orders, and political organization of polities around the world.